2007
DOI: 10.1086/520933
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureusColonization and Infection in New York State Prisons

Abstract: Methicillin-resistant Staphylococcus aureus is increasingly responsible for staphylococcal outbreaks in prison. There is limited information on the source of the outbreak strains, risk factors for infection, and transmission of these strains within a prison. We conducted a survey to determine the prevalence of nasal colonization with S. aureus in 2 New York State prisons. S. aureus isolates from clinical cultures collected from all New York State prisons during a 6-month period were compared with the colonizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
4
5

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 23 publications
1
60
4
5
Order By: Relevance
“…In Auckland, PVL-positive MSSA was strongly associated with the diagnosis of SSTI; 48% of all MSSA isolates associated with SSTI were lukSF-PV positive. The reported incidence of PVL-positive MSSA SSTI in the literature ranges from 6.8% in a teaching hospital in Michigan (14) to 93% in a New York prison endemic with the PVL-positive USA300 MSSA strain (19). The 2006 New Zealand Census revealed that the total population of Auckland consisted of the following ethnic groups: 61% European, 7% Maori, 11% Pacific, and 21% Asian (24).…”
Section: Discussionmentioning
confidence: 99%
“…In Auckland, PVL-positive MSSA was strongly associated with the diagnosis of SSTI; 48% of all MSSA isolates associated with SSTI were lukSF-PV positive. The reported incidence of PVL-positive MSSA SSTI in the literature ranges from 6.8% in a teaching hospital in Michigan (14) to 93% in a New York prison endemic with the PVL-positive USA300 MSSA strain (19). The 2006 New Zealand Census revealed that the total population of Auckland consisted of the following ethnic groups: 61% European, 7% Maori, 11% Pacific, and 21% Asian (24).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies of S. aureus nasal carriage have been carried out in various geographic regions in the United States and the Netherlands (2,5,7,21,23,27,28,41). Cross-section surveys of nasal carriage prevalence and transmission mechanisms in special healthy populations are beneficial in assessing risk factors associated with S. aureus infections (2,8,13,26,(32)(33)(34)(35). Military facilities provide unique opportunities for studying S. aureus nasal colonization and transmission (11,19,52).…”
mentioning
confidence: 99%
“…The prevalence of PVL-positive S. aureus was 2.3% in Chinese hospitals, but 12.8% in Wenzhou, China Yu et al, 2008). The prevalence of PVL-positive strains of S. aureus in Japan, Africa and the USA was 0.04, 14.7 and 48.3% (Kawaguchiya et al, 2011;Mesrati et al, 2010;Lowy et al, 2007), respectively. ST88 was the dominant clone among PVLpositive isolates.…”
Section: Mlst-ccmentioning
confidence: 94%